2022
DOI: 10.3390/challe13010009
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Realities of E-Learning during COVID-19: The Case of University Sport and Physical Education

Abstract: E-learning quickly became a crucial tool for universities and other higher education institutions during the global COVID-19 pandemic. The field of sport and physical education (PE) was no exception. However, though there is considerable growth in digital technologies in sport or physical education, we have very little evidence about the use and outcomes of these technologies. Thus, this study aims to document how e-learning technologies and pedagogical approaches were employed in the field of sport, the chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 43 publications
1
74
0
1
Order By: Relevance
“…Regarding the case of sports and physical education, there is very little evidence on the use and outcomes of the application of digital technologies. Moustakas & Robrade (2022) presented a study to describe how e-learning technologies and pedagogical approaches were used in the sports field. According to their statistical analysis, the results showed that variety and interaction were critical factors of success in the learning-teaching process.…”
Section: Related Workmentioning
confidence: 99%
“…Regarding the case of sports and physical education, there is very little evidence on the use and outcomes of the application of digital technologies. Moustakas & Robrade (2022) presented a study to describe how e-learning technologies and pedagogical approaches were used in the sports field. According to their statistical analysis, the results showed that variety and interaction were critical factors of success in the learning-teaching process.…”
Section: Related Workmentioning
confidence: 99%
“…Since 2019, Covid-19 has led to an increase in the use of e-learning. Several tools were used to conduct evaluations and written examinations [7][8][9]. Nevertheless, the reliability of these surveys as Big Data and mathematical models to improve predictions would be impacted by the savings in expenses, effort, and time that these online evaluations provide.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that 71% of public school children in the United Kingdom received no or fewer than one online lesson per day, while in Germany, just 6% of students received online lessons every day and more than half had them no more than once a week. Some economists believe that students in the United States will return to school in 2020 with an average learning gain of 70% compared to a regular school year [7]. Only a 50 percent boost in arithmetic learning may be expected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The football3 MOOC follows in a growing but still limited line of online learning offers related to sport for development, including from the Swiss Academy for Development [24], the German Corporation for International Cooperation (GIZ) [25] and others [19,20]. However, sport remains an inherently physical, practical, and interactive area, and these features do not always easily translate to the online setting [26,27]. The social and sustainable development goals typically associated with SFD also add another layer of complexity.…”
Section: Introductionmentioning
confidence: 99%